Narcissism and life satisfaction in college students: mediating role of social media addiction - Adeeb, Muhammad; Waris, Sana; Asmat, Alia; Rafiq, Saria; Hafeez, Sadaf (Journal of Pakistan Psychiatric Society, 2020)
OBJECTIVEPresent study aims to examine the association between narcissism and life satisfaction among college students: mediating role of social media addiction.STUDY DESIGN Correlational research design.PLACE AND DURATION OF THE STUDYData were collected from two government colleges of Faisalabad and Jaranwala from January 2019 to February 2019.SUBJECTS AND METHODSThe sample of this study was comprised of 233 college students from two public sectors colleges (Jaranwala = 113 and Faisalabad = 120). Three research questionnaires were used to collect the data; Narcissistic Personality Inventory, Satisfaction with Life Scale and Social Media Addiction Scale.RESULTSThe results showed that narcissism was significantly positively (moderate) correlated with social media addiction and significantly negatively (weak) correlated with life satisfaction among college students. Whereas, social media addiction was significantly and negatively (moderate) correlated with life satisfaction. Mediation analysis revealed that social media addiction is a significant and partially mediator between narcissism and life satisfaction among college students.CONCLUSIONNarcissists are going to have less satisfaction with their lives, if a person is addicted to social media, worsen the course of narcissism and would have negative impact on satisfaction with their life.